Os processos da qualidade total numa instituição de ensino na percepção dos gestores do curso de administração: um estudo no centro universitário Feevale - Mello, Maura Regina de (2004)
The current work has the aim to analyse the Quality Management System of the Business Administration Course under Feevale s manager group perception. I have carefully remarked how that group perceives the total quality management at the Institution as well as if the management paradigm applied there can be done for the activities whose product is knowledge. Data and information were collected from documentary analysis on and not structuralized interviews with the coordinators of Business Course; this way the goals considered for that study were reached. Brief, the analysis elaborated from the raised data made possible to verify the factors that contribute and the ones that make difficult the management of the total quality at Feevale, once Business Administration Course is considered as target of the quality system. Also, having followed the managers opinion and bibliography, it was possible to present some concerns to help the Quality Management at that Institution.